(untitled) (The Pakistan Development Review, 1994)
Intra-household allocations appear to be quite important in the determination of time use, human resource investments, and intra- and inter-generational transfers in developing countries. The nature of such allocations has important implications for the efficiency, equity, and efficacy of the micro and macro-economic policies. In the past decade and a half, there has been substantial progress in modelling intrahousehold allocations in ways that lead to testable propositions despite enormous data limitations regarding the nature of the allocation of unobserved variables and the impact of unobserved heterogeneous endowments. The parent -child exchange literature is a subset of these studies that advances in two dimensions by allowing children to have different preferences from their parents’ and by incorporating a broader notion of interactions, including the attention provided by the children to their parents. Yet this literature has most of the problems that are indicated with regard to the unified household preference models. The exchange literature to date has assumed away het" erogeneity in endowments which plays such a critical role in the studies that assume the unified household preferences. It is also silent on how human resource investments enter into the relations between parents and children. The collective models of household behaviour emphasise that different household members. usually husband and wife. may have different preferences and a different command over resources. Interesting theoretical results have been derived concerning the conditions under which the income-sharing rules and the allocation of non-assignable goods can be derived. But there are many limitations in this literature. The literature on the collective models of household behaviours is static and gives little consideration to the dynamic processes and learning.